2014
DOI: 10.1016/j.jad.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Do the dissociative side effects of ketamine mediate its antidepressant effects?

Abstract: Background The N-methyl-D-aspartate receptor antagonist ketamine has rapid antidepressant effects in major depression. Psychotomimetic symptoms, dissociation and hemodynamic changes are known side effects of ketamine, but it is unclear if these side effects relate to its antidepressant efficacy. Methods Data from 108 treatment-resistant inpatients meeting criteria for major depressive disorder and bipolar disorder who received a single subanesthetic ketamine infusion were analyzed. Pearson correlations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
175
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(200 citation statements)
references
References 33 publications
13
175
5
1
Order By: Relevance
“…One retrospective study has found that intra-infusion dissociation predicts antidepressant response 4 hours and 7 days later. 171 The cognitive effects of ECT in our study were milder than might have been expected from the literature and it is possible that the now widespread use of a pulse width of 0.5 milliseconds for ECT in the UK results in less effect on cognition than 1-millisecond and 1.5-milliseconds pulse widths used historically (as has recently been proposed by others 171 ). Although studies have been carried out comparing ultra-brief-pulse (0.25-0.3 milliseconds) and brief-pulse (typically ≥ 1 millisecond) ECT, we are not aware of a direct comparison between 0.5 milliseconds and longer-duration brief-pulse stimuli; this may be indicated to ascertain the optimal range of the pulse width used to minimise cognitive effects while maintaining efficacy.…”
Section: Implications For Researchsupporting
confidence: 52%
“…One retrospective study has found that intra-infusion dissociation predicts antidepressant response 4 hours and 7 days later. 171 The cognitive effects of ECT in our study were milder than might have been expected from the literature and it is possible that the now widespread use of a pulse width of 0.5 milliseconds for ECT in the UK results in less effect on cognition than 1-millisecond and 1.5-milliseconds pulse widths used historically (as has recently been proposed by others 171 ). Although studies have been carried out comparing ultra-brief-pulse (0.25-0.3 milliseconds) and brief-pulse (typically ≥ 1 millisecond) ECT, we are not aware of a direct comparison between 0.5 milliseconds and longer-duration brief-pulse stimuli; this may be indicated to ascertain the optimal range of the pulse width used to minimise cognitive effects while maintaining efficacy.…”
Section: Implications For Researchsupporting
confidence: 52%
“…The transient psychometric effects are frequently found during the administration of ketamine and shortly afterwards (Luckenbaugh et al, 2014;Sos et al, 2013;Zarate et al, 2006). Therefore, measuring ketamine's effects only during or soon after its administration might be misleading, as it is hard to interpret whether findings reflect ketamine's acute dissociative effects or more specifically on antidepressant properties.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, Luckenbaugh et al (2014) indicated that dissociative effects predicted a sustained antidepressant response. Subjects in this study who were experienced ketamine users received doses in accordance with the NIMH protocol that produced relatively mild dissociative symptoms, and most of these reported only minimal beneficial impact.…”
Section: International Journal Of Transpersonal Studies 80mentioning
confidence: 89%